Motivational strategies as correlates of senior secondary school geography students' achievement (2011)
The study investigated the level of teachers' awareness and utilization of motivational strategies and their influence on secondary school students' cognitive achievement in geography. Eight one geography teachers who were randomly selected from the six geopolitical zones of Nigeria participated in the study. The teachers responded to awareness as well as utilization of motivational strategies' scales, while Geography achievement test was administered on the students. Frequency counts, percentages and multiple regression were used to analyse the data. Results shopwed that over 85% of the teachers were aware of motivational strategies that can be used to enhance students' learning. Teachers' level of utilisation of relevant teaching materials strategies was, however, poor. Teachers' use of statistically significantly significant effect on cognitive achievement in geography. Findingd in this study ahve implications for introduction of capacity building that will delve into emergent educational issues that can be used to solve instructional problems in the classroom. These should be organised through regular training and re-training programmes for teachers.